Molecular characterization and genome organization of 7SL RNA genes from hop (Humulus lupulus L.) - Matousek, J; Junker, V; Vrba, L; Schubert, J; Patzak, J; Steger, G (Gene, 1999)
A wide spectrum of hop 7SL RNA-encoding sequences was detected by temperature gradient-gel electrophoresis. Four hop 7SL RNA genes were cloned and characterized. A new subvariant of the upstream sequence element (USE) 5'TCCCACATGG 3' and two distinct variants of TATA signal were found at positions characteristic for RNA polymerase III-driven transcription in plants. In addition, a more distant conserved sequence element 5' CATGTATAAACTTTCTGC 3' was present in all cloned genes, about 160 bp upstream of the 7SL RNA coding sequence. Consensus secondary structures calculated for hop 7SL RNAs revealed characteristic features, although some structure differences from formerly published models were predicted. Specific in-vitro transcription of plant 7SL RNA genes was observed in a heterologous system (HeLa extract). This in-vitro transcription assay showed significant differences among individual clones in transcription rates, suggesting the requirement of complexity of 7SL RNA sequence for its efficient transcription in HeLa extract. Southern blot analysis of hop DNA revealed 12 7SL-specific signals corresponding to HindIII fragments ranging from 0.45 to 7.8 kb. Several 7SL RNA-encoding sequences and various intergenic spacers were amplified from the individual HindIII fragments of about 1.3 and 2.8 kb. These facts suggest that at least some of the hop 7SL RNA genes are organized in genomic clusters.
Keywords: HeLa Cells; Base Sequence; DNA, Plant; Genome, Plant; Molecular Structure; Transcription, Genetic; lidé; HeLa buňky; Molecular Sequence Data; RNA, Small Cytoplasmic; Nucleic Acid Conformation; signál-rozpoznávající částice; Genes, Plant; konformace nukleové kyseliny; Phylogeny; Blotting, Southern; molekulární struktura; rostlinné geny; genetická transkripce; molekulární sekvence - údaje; RNA malá cytoplazmatická; Cloning, Molecular; sekvenční homologie nukleových kyselin; Sequence Alignment; DNA rostlinná; Rosales; sekvence nukleotidů; Sequence Homology, Nucleic Acid; Sequence Analysis, DNA; Southernův blotting; klonování DNA; sekvenční analýza DNA; Signal Recognition Particle; fylogeneze; genom rostlinný; sekvenční seřazení; Humans